2007
DOI: 10.1111/j.1527-5299.2007.05948.x
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Hemodynamic Response and Reduced Oxygen Delivery With Exercise in Anemic Heart Failure Patients With Systolic Dysfunction

Abstract: Anemic heart failure patients with systolic dysfunction are known to have reduced exercise capacity. Whether this is related to poor hemodynamic adaptation to anemia is not known. Peak exercise oxygen consumption (VO2) and hemodynamics at rest and peak exercise were assessed among 209 patients and compared among those who were (n=90) and were not (n=119) anemic. Peak VO2 was significantly lower among anemic patients (11.7±3.3 mL/min/kg vs 13.4±3.1 mL/min/kg; P=.01). At rest, right atrial pressure was higher (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Animal studies suggest that RV pressure overload leading to increasing RA size is more closely related to RV diastolic dysfunction (19). Impaired RV contractility may cause compensatory elevated RAVI for increasing blood volume reservoir, and result in an underperfused state with lower blood volume or oxygen delivery from the pulmonary circulation (20,21). The dilated RA size and depressed RV ejection function may present as reduced exercise tolerance (22).…”
Section: Figure 1 Ravi According To Severity Of Rv and LV Dysfunctionmentioning
confidence: 99%
“…Animal studies suggest that RV pressure overload leading to increasing RA size is more closely related to RV diastolic dysfunction (19). Impaired RV contractility may cause compensatory elevated RAVI for increasing blood volume reservoir, and result in an underperfused state with lower blood volume or oxygen delivery from the pulmonary circulation (20,21). The dilated RA size and depressed RV ejection function may present as reduced exercise tolerance (22).…”
Section: Figure 1 Ravi According To Severity Of Rv and LV Dysfunctionmentioning
confidence: 99%
“…In contrast, only 64.7% of those with anaemia and elevated BNP (p < 0.001) survived, representing a 10.4-fold increased risk of death. Listerman et al [20] evaluated 209 HF patients with an ejection fraction of ≤40% who underwent haemodynamic exercise testing and reported that the resting right atrial pressure was higher (10 mm Hg vs. 8 mm Hg; p � 0.02) and the exercise peak VO 2 was significantly lower (11.7 mL/min/kg vs. 13.4 mL/min/kg; p � 0.01) among the anaemic patients. No significant differences in parameters characterising cardiac output (stroke volume and cardiac index) at peak exercise were observed between anaemic and nonanaemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, any reason for impaired oxygen delivery process such as anaemia would exacerbate the ischemic component in patients with LVSD (Fig. 1) [20].…”
Section: Significance Of Left Ventricular Systolic Dysfunction In Pat...mentioning
confidence: 99%
“…In a single centre non-randomized study conducted on 65 patients with intermediate coronary lesions, patients were divided based on left ventricular end diastolic pressure (LVEDP) cut-off of 15 mmHg [26]. A discordant result of FFR and instantaneous free wave ratio was more frequently recorded among patients with elevated compared to normal LVEDP (42.8% vs. 6.7%, p = 0.001) [20]. Whilst FFR is defined as the ratio of distal over proximal hyperemic flow in relation to the coronary lesion, in clinical practice mean proximal and distal arterial pressure is used as a surrogate of flow.…”
Section: Ischemia Assessment In Lvsdmentioning
confidence: 99%